IMPLEMENTASI METODE CERITA ISLAMI DALAM PENANAMAN NILAI NILAI PENDIDIKAN AGAMA ISLAM DI RAUDLATUL ATFAL - anwar, Ahmad; Almurtaqi, Moch Ridwan; Muchlisin, Imam (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2023)
The application of the Islamic story method can be used as an alternative learning method used in cultivating Islamic religious education. This research is qualitative descriptive research and library research. The data comes from various reading sources, book articles and other sources. The results of the research are: Implementation of the story method in instilling the values ​​of Islamic religious education must be planned as well as possible, both through the story method and Islamic stories for students. This method is very effective in conveying teachings about morals and faith. Providing a good example to students, it can also be through the teacher's profile or good attitude and behavior, it is hoped that students will imitate it, without the teacher providing an example of moral development it will be very difficult to achieve.